Ctrl+AI+Learn: Contextualizing Generative AI Policies for Incoming University Students - Enaya, Talla; Seeley, Sarah (Discourse and Writing/Rédactologie, 2025)
This teaching report describes a workshop delivered at the University of Toronto Mississauga as a part of the Robert Gillespie Academic Skills Centre’s (RGASC) Head Start program. The workshop was premised on two guiding ideas: (1) since the University of Toronto maintains flexible guidelines regarding generative AI (hereafter genAI) policies across courses, undergraduate students benefit from participation in candid discussions of the contextual nature of shifting technological values and (2) first-year university students are in the unique position of also needing to contextualize the shift from high school to university learning contexts, so they are in particular need of opportunities to discuss the diversity of perspectives surrounding the permissibility of genAI use in higher education. The workshop led students through noticing the differences between high school and university learning expectations; applying socially oriented theories of communication; contextualizing “local” genAI syllabus policies; and crafting a personal theory of acceptable genAI use. This report is a collaboration between an undergraduate student (Author 1) and a writing professor (Author 2). To support educators in replicating all or part of this exercise within their own local contexts, workshop materials are appended.